(untitled) (Journal of Contemporary Educational Policies and Practices, 2021)
As a great challenge to most English learners, speaking skills have aroused the interest of numerous researchers in many countries where English is taught as a foreign language. This study aimed to investigate some difficulties that students faced in speaking classrooms. A group of 57 participants at Tra Vinh university was selected to complete the questionnaires to find out students’ speaking problems from psychological and linguistic perspectives and 12 of them participated in the face-to face interviews. The results from the questionnaire revealed that non-English majors encountered more linguistic difficulties than psychological ones. Also, students’ psychological problems identified includes: pressure to perform well, being overpowered by more competent students, fear of making mistakes in front of the class and fear of criticism or losing face. The linguistic difficulties are lacking vocabulary and topical knowledge, being uncapable of arranging ideas logically, insufficient sentence formation skills and inappropriate vocabulary. The findings from the interview also showed that learners encountered more linguistic difficulties. Based on the findings above, some possible solutions are suggested to assist students in improving their speaking skills when acquiring English.